Mean fatigue lives of steel fibrous concrete containing blends of limestone powder, metakaolin and silica fume - Kaur, G.; Singh, S.P.; Kaushik, S.K. (Journal of Structural Engineering, 2024)
The present study constitutes an experimental work that aims to report the effect of mineral additives like limestone powder (LP), metakaolin (MK) and silica fume (SF) on the flexural fatigue performance of concrete. To carry out the study, these mineral additives were applied in the range of 0 to 30% to replace cement in different proportions. In total, four mix combinations have been prepared with the one containing 100% ordinary Portland cement (OPC) termed as control mix. Approximately 192 flexural fatigue tests and 96 complementary static flexural tests were executed on beam specimens of size 100mm x 100mm x 500mm under three point flexural loading arrangement. It has been observed that the probabilistic distribution of fatigue life data of all mix combinations, at a given stress level (S), can approximately be modeled by two-parameter Weibull distribution. The graphical method and the method of moments have been used to determine distribution parameters. The mean fatigue lives of all mix combinations have also been estimated at different stress levels. The replacement of OPC by these mineral additives not only lowers the cost and enhances greenness in concrete but also reported reduced variability in fatigue life distribution and improved mean fatigue life values as compared to control concrete. The mix containing 20% LP and 10% SF as partial cement replacements, also designated as CLS, has been considered most appropriate one in terms of maximum reduction of variability in the distribution of fatigue life and increased mean fatigue life. In general, the improved multi-powder particle size distribution, particle effect and pozzolanic effect of mineral additives produce synergistic effect.